THE SOLAR‐TO‐STREAM POWER RATIO: A DIMENSIONLESS NUMBER EXPLAINING DIEL FLUCTUATIONS OF TEMPERATURE IN MESOSCALE RIVERS. (21st May 2012) - Link, O.; Huerta, A.; Stehr, A.; Monsalve, A.; Meier, C.; Aguayo, M.
ABSTRACT The diel variation of temperature in mesoscale river reaches (catchment area > 1000 km2) is analysed using concurrent measurements of water temperature and of those meteorological (incident short‐wave radiation, air temperature, relative humidity and wind speed variables) and hydraulic variables (streamflow, top width, channel slope and flow depth) controlling the thermal regime. Measurements were taken along two river reaches located in central Chile, on the Itata (11 290 km2, Strahler's order 6, reach length 30 km, Qbankfull = 400 m3 s−1) and Vergara (4340 km2, Strahler's order 5, reach length 20 km, Qbankfull = 85 m3 s−1) rivers. The measuring frequency was 15 min. The relevant energy fluxes at the air–water interface, that is, atmospheric long‐wave radiation, net short‐wave radiation, radiation emitted by the water body, evaporation (latent heat) and conduction heat are computed and analysed for four scenarios of 12 days duration each, representing typical conditions for the austral winter, spring, summer and autumn. We find large differences in the diel river temperature range between the two sites and across seasons (and thus, flows and meteorological conditions), as reported in previous studies, but no clear relationship with the controlling variables is overtly observed. Following a dimensional analysis, we obtain a dimensionless parameter corresponding to the ratio of solar‐to‐stream power, which adequately explains the diel variation of water temperature in mesoscale rivers. A number of our own measurements as well as literature data are used for preliminary testing of the proposed parameter. This easy‐to‐compute number is shown to predict quite well all of the cases, constituting a simple and useful criterion to estimate a priori the magnitude of temperature diel variations in a river reach, given prevailing meteorological (daily maximum solar radiation) and hydrologic–hydraulic (streamflow, mean top width) conditions. Copyright © 2012 John Wiley & Sons, Ltd.